A Review on Mouth Dissolving Tablets and Meloxicam - Shubham Saini,; Manmohan Sharma,; Anil Ahuja,; Ashok Kumar, (Asian Journal of Pharmaceutical Research and Development, 2025)
Mouth dissolving tablets (MDTs) have emerged as a novel dosage form designed to enhance patient compliance and therapeutic efficacy, particularly for pediatric, geriatric, and dysphagic patients. These tablets rapidly disintegrate in the oral cavity within seconds, releasing the drug for quick absorption without the need for water. Meloxicam, a non-steroidal anti-inflammatory drug (NSAID) belonging to the oxicam class, exhibits poor water solubility and delayed onset of action when administered as conventional tablets. The development of Meloxicam MDTs aims to overcome these limitations by improving solubility, enhancing bioavailability, and providing rapid analgesic and anti-inflammatory effects. This review highlights the fundamental principles of MDT formulation, including the role of super-disintegrants, excipients, and formulation techniques such as direct compression and lyophilization. It also discusses evaluation parameters, challenges in taste masking, and recent advancements in fast-dissolving technology. The study concludes that MDTs of Meloxicam represent a promising alternative to conventional oral dosage forms, offering rapid onset, improved patient acceptability, and better therapeutic performance.